Culture and identity: Two different notions - Grimson, Alejandro (2010)
A clear, precise conceptual distinction between 'culture' and 'identity' is an essential precondition for analyzing social processes. The anthropological concept of 'identity' has been built up over time and enriched by studies on interethnic relationships, ethnic borders and ethnicity. The objective of this essay is to add to an already well-defined concept of culture by incorporating decisive contributions from theories on the nation. Culture and nation are not only highly complex theoretical notions with a long history; they both deal with heterogeneous and conflictive entities. The essay asserts that culture and identity allude to analytically different aspects of social processes. No relationship between the two can be presupposed or generalized to fit all cases. It is necessary to analyze cultural and identitary aspects separately. © 2010 Taylor & Francis.